2019
DOI: 10.1111/srt.12661
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency (20‐MHz) high‐intensity focused ultrasound (HIFU) system for dermal intervention: Preclinical evaluation in skin equivalents

Abstract: Background High‐intensity focused ultrasound (HIFU) for non‐invasive treatment of a range of internal pathologies including cancers of major organs and cerebral pathologies is in exponential growth. Systems, however, operate at relatively low frequencies, in the range of 200‐2000 kHz as required for deep axial penetration of the body. HIFU utilizing frequencies in excess of 15 MHz has so far not been explored, but presents an opportunity to extend the HIFU modality to target specific dermal lesions and small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 27 publications
(33 reference statements)
0
45
0
3
Order By: Relevance
“…Preclinical testing indicated a realistic range of operation within a dose range of 0.6-1.5 J/dose in the clinic. 23,26 The method produced the intended thermic insults in the dermis and was confirmed as ablative or non-ablative depending on setting and choice of transducer. In the pig model, scarring was not a problem, albeit histology revealed subclinical fibrous change in cases exposed to high-energy multiple doses positioned in close proximity to each other.…”
Section: F I G U R E 1 Schematic Illustration Of the High-intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical testing indicated a realistic range of operation within a dose range of 0.6-1.5 J/dose in the clinic. 23,26 The method produced the intended thermic insults in the dermis and was confirmed as ablative or non-ablative depending on setting and choice of transducer. In the pig model, scarring was not a problem, albeit histology revealed subclinical fibrous change in cases exposed to high-energy multiple doses positioned in close proximity to each other.…”
Section: F I G U R E 1 Schematic Illustration Of the High-intensitymentioning
confidence: 99%
“…This requires an operating frequency of at least 15 MHz as confirmed by theoretical considerations and preclinical testing. 22,23 Commercially available HIFU systems for aesthetic wrinkle reduction and body contouring operate at about 3-10 MHz. Such frequencies create focal zones that exceed the total thickness of the skin, and are therefore not feasible for dermatology indications addressing the dermal end epidermal layers only.…”
mentioning
confidence: 99%
“…It has recently been demonstrated that a new HIFU device operating at 20 MHz shows promise for treating indications requiring much lower focal distances and smaller focal zones. This HIFU modality therefore becomes relevant for the field of dermatology . The principle and relevance of high‐frequency HIFU used in dermatology are illustrated in Figures and .…”
Section: Introductionmentioning
confidence: 99%
“…In the high‐frequency HIFU introduced in the above mentioned pre‐clinical study, real‐time monitoring is integrated in the system using a digital video camera that operates as a surface microscope or dermascope. Using a pointer in the camera, and observing the skin surface above the lesion, the HIFU shot can be positioned precisely in the target, and a whitening or contraction of the treated point can be observed on the surface after each dose.…”
Section: Introductionmentioning
confidence: 99%
“…This method focuses on applying heat to areas through acoustic energy to areas of the deep dermis, subdermal connective tissue, and fibromuscular layer in targeted microcoagulation zones without effect to the epidermis. 47 The targeted thermal effects and microcoagulation are believed to cause skin tightening through collagen contraction and remodeling. Future studies are needed to determine the overall benefits in skin laxity to achieve approval by the US Food and Drug Administration for use as a treatment option.…”
Section: Ultrasoundmentioning
confidence: 99%